Group cohesion and athlete development - Eys, M.; Loughead, T. M.; Godfrey, M. (Routledge handbook of talent identification and development in sport, 2017)
The concept of cohesion is, for good reason, considered a group variable. This is for good reason. It is an emergent property of groups resulting from (and influencing) teamwork processes (McEwan & Beauchamp, 2014), and is facilitated by creating an effective structure marked by clear role responsibilities for group members and strong leadership (Carron & Eys, 2012). However, there is ample evidence in the popular media and in the extant academic literature demonstrating links between the team environment, as represented by cohesion, and important individual athlete outcomes. For example, in explaining the European Ryder Cup win over the United States in 2004, golfer Colin Montgomerie stated "We`re one of the closest teams in international sport. ... It`s amazing how well we play for each other" (Shipnuck, 2004, para. 3). Traditionally, golf is not the first sport one thinks of when considering the concept of cohesion. In this example, however, individual performances/behaviors were thought to be enhanced because of the perceived unity and togetherness of this European golf team. The various sources and levels of interdependence among roup members within sport teams (e.g., task, outcome, and resource interdependencies; Evans, Eys, & Bruner, 2012) allow not only for group dynamics to emerge, but also for those group dynamics to reciprocally influence the members (Cronin, Weingart, & Todorova, 2011). The objective of the present chapter, in line with the general purpose of the current text, is to highlight how the group environment affects the development of athletes based on relationships demonstrated between cohesion and individual cognitive, affective, and behavioral outcomes. In essence, after highlighting general principles regarding the concept of cohesion, we make the case that an athlete`s development will be inextricably linked to the groups he or she joins.